THE INFLUENCE OF EDMODO AS A COMPLEMENTARY TOOL IN LEARNING ENGLISH TO THE STUDENTS’ PERCEPTION OF NURSING SCIENCE PROGRAM AT STIK BINA HUSADA PALEMBANG - Agus Wahyudi (Language and Education Journal, 2018)
Rapid advances in science and technology bring radical changes in how to live, especially how we communicate. One of the most vital ICT contributions in education is the ease of access to teaching and learning. Edmodo is an educational site that takes the idea of a social network and refines and makes it appropriate for the class. The research method used in this research was an experimental method. The design used is one group pretest-posttest design. The population of this study was students of Nursing Science Program, STIK Bina Husada Palembang, the third semester in 2017/2018 academic year, the sample of this study was 48 students. The instrument of this study was a questionnaire adapted from Enriquez (2014) by using the Likert scale. After students fill out the questionnaire, univariate and bivariate analyzes were run. The collected data was analyzed by using t-test to find out whether the mean value differed significantly. The pretest result showed that there were 19 students or 40% in the negative category and 29 students or 60% in the positive category. The posttest result showed that 2 students or 4% were in the negative category and 46 students or 96% were in a positive category. The mean value of the pretest was 37.40, the standard of deviation was 3.972, while the mean of the posttest was 48.44, and the standard deviation was 4.522. The statistical value showed 0.000, hence it can be concluded that there was a significant difference between before and after given treatment